Physico-chemical and Antifungal Investigation of Metal Complexes of Co(II), Ni(II) and Cu(II) with Schiff Base - RAI, B.K.; RAI, RAJESHWAR; SAHI, POONAM; RANA, SWATY (Asian Journal of Chemistry, 2010)
In this paper, the synthesis of Co(II), Ni(II) and Cu(II) complexes with 2-phenyl[3-(hydroxyl propyl)]-3,1-(4H)-quinazolin- 4-one semicarbazone/thiosemicarbazone (PHQS/PHQTS) is reported. Structural characterization has been done on the basis of elemental analysis, IR, electronic spectra, magnetic susceptibility, molar conductance data. Complexes have been proposed to be octahedral in geometry. The ligand as well as complexes were screened for their antifungal studies.